Restoring the Esthetics in Hemiparalytic Patient with Detachable Prosthesis - Dewan, Smriti Kapur; Sehgal, Monika; Arora, Aman; Garg, Sushant; Arora, Sheen Juneja; Seth, Neha (Journal of Orofacial Research, 2013)
Emphasis on facial esthetics has become an integral part of dental treatment. Restoring and improving facial appearance of a complete edentulous patient with hollow cheeks is achallenge to the prosthodontist. Thus, to improve patient’s lower lip contour that was paralyzed and to improve patient’s oral competency, a detachable prosthesis was fabricated. This clinical report describes the procedure for making a lip plumper prosthesis to improve patient esthetics, oral function.